A pH-Activatable nanoparticle for dual-stage precisely mitochondria-targeted photodynamic anticancer therapy. (August 2019) - Qi, Tong; Chen, Binlong; Wang, Zenghui; Du, Hongliang; Liu, Dechun; Yin, Qingqing; Liu, Bangyuan; Zhang, Qiang; Wang, Yiguang
Abstract: Mitochondria-targeted photodynamic therapy (PDT) has emerged as one of the most efficient antitumor strategies. However, the therapeutic outcome of mitochondria-targeted PDT nanocarriers has been hampered by its poor capability of endosome escape and always-ON mode which induces normal tissue damage. To tackle these limitations, herein a novel pH-activatable nanoparticle is developed with dual-stage targeting capacity of early endosome and mitochondria for exponential activation of fluorescent signals and photodynamic efficacy. This nanoparticle is composed of pH-responsive mPEG- b -PDPA-Cy7.5 fluorescent copolymer and mitochondria-targeted photosensitizer (TPPa). The TPPa-encapsulated nanoparticles (M-TPPa) exhibit 111- and 151-fold enhancement in fluorescent signal and singlet oxygen generation (SOG) on encounting acidic pH environment, respectively. The M-TPPa can be quickly endocytosed by cancer cells and immediately dissociate at acidic early endosome to activate fluorescent signals and photoactivity. Subsequently, the activated TPPa quickly translocates from early endosome to mitochondria. Under laser irradiation, singlet oxygen could be generated in mitochondria, inducing intrinsic apoptosis in human HO8910 ovarian cancer cells. M-TPPa also exhibits high tumor imaging contrast and remarkable inhibition on tumor progression without obvious toxicity in HO8910-tumor bearing mice. Therefore, the rationally designed nanoparticles, with precise dual-targeting of distinct organelles and theranostic signal amplification, provides a promising strategy for efficient cancer treatment. Graphical abstract: Image 1 Highlights: Over 100-fold amplification in both fluorescence and photoactivity signals. Sequential precise accumulation in early endosome and mitochondria. Efficient targeting to mitochondria in 30 min.